Поставьте на черное: [роман] / Лев Гурский - Гурский Лев Аркадьевич (Д. Д. Д., 1999)
Экземпляры: ф.9 (20200325) / Инвентарный номер: 58886 / Цена: 10.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Г 95 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-4